Cover Image. (29th January 2018) - Unknown
Abstract : Cover Illustration: The image illustrates the massive influx of effector cells around the larvae during a protective secondary infection with N. brasiliensis. Eosinophils and macrophages (that are positive for F4/80 in the lung) are recruited and activated by the cytokines made by ILC2s during a helminth infection.